Oud instrument interventions for healing purposes : a systematic literature review - Muhammad Asyraf Mohd Bakri; Kamal Sabran (Penerbit Universiti Kebangsaan Malaysia, 2022)
Oud, short-necked, and frantic “lute” fret-less lute is traditional instrument music come from the Middle East, which has many advantages over humans. The ‘King of Instruments’ in Islamic civilization is the most commonly used and most important musical instrument among the Arabs. The aim of the present study of the current systematic survey aims to find out the types of research related to the use of Oud musical instruments for healing purposes. This article analyzed the recent literature on advantage instrument music Oud for healing purposes. Guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) research process, a systematic review of the Scopus, Science Direct, PubMed, ProQuest, Springer and EBSCO databases, including those relating to well-being, health, art interventions, 6 related studies. Oud instrument has three benefits for healing purposes. Result shows, in terms of well-being, the average indicates tool helps by showing the constructive impact on the recipient's psychology. In terms of health, the Oud instrument helps by showing a positive effect on the patient's health. In terms of art intervention, the Oud instrument is seen to help in the suitability of the desired music. In conclusion, while there has been no study done on the use of Oud musical instruments in music therapy, despite the fact that these musical instruments have been available for a long time and are increasing in popularity around the world, there is still no research on their use in music therapy.